Fatal COVID-19 in a Child with Persistence of SARS-CoV-2 Despite Extensive Multidisciplinary Treatment: A Case Report - Sofia Apostolidou; Theresa Harbauer; Peter Lasch; Daniel Biermann; Maja Hempel; Marc Lütgehetmann; Susanne Pfefferle; Jochen Herrmann; André Rüffer; Konrad Reinshagen; Rainer Kozlik-Feldmann; Anna Gieras; et al. (MDPI AG, 2021)
Critical Coronavirus disease 2019 (COVID-19) developed in a 7-year-old girl with a history of dystrophy, microcephaly, and central hypothyroidism. Starting with gastrointestinal symptoms, the patient developed severe myocarditis followed by progressive multiple organ failure complicated by Pseudomonas aeruginosa bloodstream infection. Intensive care treatment consisting of invasive ventilation, drainage of pleural effusion, and high catecholamine therapy could not prevent the progression of heart failure, leading to the implantation of venoarterial extracorporeal life support (VA-ECLS) and additional left ventricle support catheter (Impella® pump). Continuous venovenous hemofiltration (CVVH) and extracorporeal hemadsorption therapy (CytoSorb®) were initiated. Whole exome sequencing revealed a mutation of unknown significance in DExH-BOX helicase 30 (DHX30), a gene encoding a RNA helicase. COVID-19 specific antiviral and immunomodulatory treatment did not lead to viral clearance or control of hyperinflammation resulting in the patient's death on extracorporeal life support-(ECLS)-day 20. This fatal case illustrates the potential severity of pediatric COVID-19 and suggests further evaluation of antiviral treatment strategies and vaccination programs for children.